1939
DOI: 10.6028/jres.023.016
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of crucibles from special refractories by slip-casting

Abstract: The slip-casting process, which is widely used in ceramics, has not been generally applied to the preparation of crucibles from special refractories, which lack the property of plasticity. However, enough plasticity to make slip-casting feasible can be developed in some of the special r efractories by fine grinding and treatment with acid. Thin-walled crucibles of alumina, beryllia, zircon, zirconia, and electrically fused thoria were cast from aqueous slips, and bricks 5 cm thick were made by a modified proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1944
1944
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…During the 1930s research on the processing side of casting and forming ceramics for more advanced applications was carried out. Slip casting was seen as a viable method in producing ceramic crucibles for use in casting refractories . The surface finish associated with the traditional forming methods such as pressing or tamping produced a degree of roughness that would lead to premature fractures.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the 1930s research on the processing side of casting and forming ceramics for more advanced applications was carried out. Slip casting was seen as a viable method in producing ceramic crucibles for use in casting refractories . The surface finish associated with the traditional forming methods such as pressing or tamping produced a degree of roughness that would lead to premature fractures.…”
Section: Introductionmentioning
confidence: 99%
“…The surface finish associated with the traditional forming methods such as pressing or tamping produced a degree of roughness that would lead to premature fractures. For this reason, Thompson and Mallett applied the slip casting process to produce thin walled crucibles along with thick cross‐section bricks of Al 2 O 3 , beryllia (BeO), zircon (ZrSiO 4 ), ZrO 2 , and electrically fused ThO 2 —all of which were cast from aqueous colloidal suspensions. The authors drew on Hall's review of slip casting clays that highlighted aspects such as controlling suspension impurities, found in both the solid materials and in the solution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, other workers (6) have shown that this method of treatment may be applied to other non-plastic materials than that used in this investigation. This is to be expected, since the fundamental basis of the process is the development of colloidal properties in the material used.…”
Section: Discussionmentioning
confidence: 85%
“…Similar acid treatments were used for alumina (23,24) and other refractory oxides such as ZrO2, ThO2, BeO, etc (25,26) in the 30s, as well as the use of alkaline deflocculants.…”
Section: Colloidal Processing a Historical Perspectivementioning
confidence: 99%